Health & Physical Activity - Scheer V; 2; Hoffman MD; 3 (Deutsche Zeitschrift für Sportmedizin, 2018)
Definition: Exercise-associated hyponatremia (EAH) is defined by a below-normal serum sodium concentration (< 135 mmol/L) during or up to 24 hours after physical activity.Epidemiology: Incidence varies according to type of sport ranging from 11% after an Ironman triathlon to 51% after a 161-km ultramarathon and up to 70% among rowers during training camp. EAH-related deaths have been reported. Underlying mechanism: The two main etiological factors are overhydration due to excessive intake of water and/or hypotonic beverages and an inappropriate secretion of arginine vasopressin (AVP) with water retention, resulting in dilutional hyponatremia, with a relative excess of total body water in relation to the total content of exchangeable body sodium.Symptoms: EAH can be asymptomatic or symptomatic. Early clinical signs are nonspecific and may include nausea, vomiting, dizziness, headache and body mass gain. Without proper intervention, cerebral edema with life-threatening symptoms such as confusion, agitation, seizures and coma (exercise-associated hyponatremia encephalopathy (EAHE)) may develop.Treatment: Asymptomatic EAH can be treated by fluid restriction until onset of urination, mild symptomatic cases of EAH by oralhypertonic saline solutions, while intravenous infusion of hypertonic saline can be life-saving in moderate to severe EAH and EAHE.Prevention: Proper hydration strategies like drinkinglimitedto thirst can generally prevent EAH. Education of athletes and coaches about EAH is key in preventing this condition. Education of medical staff should focus on early recognition and appropriate treatment of EAH.KEY WORDS: Prevention, Exercise, Hyponatremia, Hypertonic Saline Solution